Performance Evaluation of South African Mutual Funds: The Effects of Fees on Performance - Adams, Deen (Department of Finance and Tax, 2023)
This paper aims to evaluate the performance and the effects of fees on performance of South African equity, bond and money market mutual funds between June 2010 and July 2019. This paper tries to evaluate whether South African active mutual funds warrant their active fees. 31 equity funds, 14 bond funds and 21 money market funds are examined in order to compare the performance of the funds within the period. The fees of each of these fund categories are also analyzed along with fund performance. In order to measure these funds, the Information ratio (1973), the Sharpe ratio (1965), Jensen's alpha (1968) and the Sortino ratio (1980) methods are used. Jensen's alpha is also used in identifying selectivity skills of fund managers. None of the funds in the sample were found to outperform their respective benchmark over the sample period. Thus, because no fund was able to outperform their respective benchmark this also resulted in significant negative alphas across all fund categories. Equity funds had the highest return over bond and money market funds but were also found to have the highest fees while exchange traded funds (ETF) charged the lowest fees. The compounding effect of paying high fees was found to erode performance and to be more costly the longer the time horizon. This paper found that investment managers could not outperform their respective benchmark on a consistent, total risk-adjusted basis and took on unnecessary risk which was not rewarded in the form of higher returns. This paper concludes that passive investing style is more appropriate in South Africa as active managers were unable to justify the high active fees that they charged.